2015 IEEE International Conference on Systems, Man, and Cybernetics 2015
DOI: 10.1109/smc.2015.414
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Operator's Pain: Toward Evaluating Musculoskeletal Disorder at Work

Abstract: Abstract-Musculoskeletal disorders (MSDs) have affected an increasing number of people in the active general population. In this perspective, we developed a measuring tool taking muscle activities in certain regions of the body, standing posture taking the center of pressure under the feet and feet positions. This tool also comprises an instrumented helmet containing an electroencephalogram (EEG) to measure brain activity, and an accelerometer reporting the movements of the head. Then, our tool comprises both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The origin of musculoskeletal pain is often associated with inappropriate postures or movements [148,149,169]. Such is the case of the study reported in [150], which suggests a relation between the sitting time during the full day and specifically during work time, and the intensity of neck/ shoulder pain in workers developing manual work.…”
Section: Physical Activity As a Predictor Of Painmentioning
confidence: 71%
See 1 more Smart Citation
“…The origin of musculoskeletal pain is often associated with inappropriate postures or movements [148,149,169]. Such is the case of the study reported in [150], which suggests a relation between the sitting time during the full day and specifically during work time, and the intensity of neck/ shoulder pain in workers developing manual work.…”
Section: Physical Activity As a Predictor Of Painmentioning
confidence: 71%
“…This scenario justifies current efforts for the development of objective physical activity evaluation systems for the identification of pain-related activities (breast pain, headache, etc.) [137,138], for the evaluation of pain intensity [139][140][141][142][143][144][145][146][147], for the detection of postures, movements or activities that can produce pain [148][149][150][151][152][153], or for the improvement of quality of life and a reduction of pain intensity [154][155][156][157][158].…”
Section: Accelerometry-based Activity Evaluation and Chronic Painmentioning
confidence: 99%
“…In other studies related to the computation of the risk of fall, we also use only one enactive insole (located on the dominant limb) with successful results [ 44 ]. All this makes it possible to reduce the production cost of the device and use a minimal configuration and architecture (already presented in two other studies [ 45 , 46 ]). This allows the classification of the postures, not to optimize this configuration.…”
Section: Design Of the Measurement Systemmentioning
confidence: 99%
“…In particular, fatigue monitoring is more considered as a valuable tool in repetitive and automatic tasks such as driving, piloting or quality control (e.g., Zhang et al, 2017;Huang et al, 2019). For this reason, some solutions that integrate EEG captors within worksite helmets (e.g., Li et al, 2014;Barkallah et al, 2015) or under headwears (e.g., Zhang et al, 2017) have already been proposed to warn users whenever a critical drowsiness threshold is reached.…”
Section: Safety At Work: Passive Bcimentioning
confidence: 99%